Digital Transformation in Islamic Education Management in the Era of Society 5.0 - Sindy Rahmawati; Bunyamin (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2026)
Digital transformation in Islamic education management has become an increasingly important issue in the Society 5.0 era because the development of digital technology not only affects administrative and learning systems but also brings changes to organizational culture, leadership patterns, and the integration of Islamic values ​​in educational governance. This study aims to analyze digital transformation in Islamic education management, identify challenges and opportunities for its implementation, and explain the social, cultural, and pedagogical implications that arise in the process of digitalizing Islamic education in the Society 5.0 era. The study used a qualitative approach with the Systematic Literature Review (SLR) method. Data were obtained from various national and international journal articles relevant to the research topic through documentation techniques and literature selection based on specific inclusion criteria. Data analysis was conducted using narrative thematic analysis by identifying key themes related to management digitalization, digital leadership, learning transformation, digital literacy, and the integration of Islamic values. The results show that digital transformation in Islamic educational institutions is taking place gradually and is still dominated by administrative-operational aspects, such as the digitalization of academic services, finance, and management information systems. The success of digital transformation is greatly influenced by the quality of digital leadership, human resource readiness, digital literacy, and support from institutional infrastructure and policies. The study also found a digital divide between regions, differences in adaptation between generations of educators, and the suboptimal integration of Islamic values ​​into formal digital systems. These findings contribute to the development of digital-based Islamic education management studies by emphasizing the importance of a human-centered approach that integrates technology, Islamic ethics, and pedagogical innovation in a balanced manner. The study concluded that the digital transformation of Islamic education requires a holistic, inclusive, and values-based strategy to sustainably address the challenges of Society 5.0. Future research is recommended to use a field approach to explore the empirical experiences of Islamic education actors in greater depth.